The effect of preoperative anxiety and ovarian stimulation on gastric antrum size: a prospective observational study - Karam Azem; Sharon Orbach-Zinger; Philip Heesen; Arthur Finkelstein; Leonid A. Eidelman; Yoel Shufaro; Cristian Arzola (Taylor & Francis Group, 2023)
Pulmonary aspiration is a potentially lethal perioperative complication related to gastric size and contents. Several perioperative factors are believed to increase gastric size, while others are less studied. This prospective observational study aimed to investigate the effect of preoperative anxiety and hormone-induced ovarian stimulation on gastric size examined by gastric ultrasound. We recruited 49 female patients undergoing hormone-induced ovarian stimulation and oocyte retrieval for in vitro fertilization at Rabin Medical Centre, Petah Tikva, Israel. Preoperatively, women ranked their anxiety level using a verbal numeric anxiety score (VNS). In addition, we recorded the extent of ovarian stimulation and measured the antral cross-sectional area (CSA) using gastric ultrasound. There was no substantial correlation between preoperative VNS anxiety and antral CSA (p = .697). Moreover, the number of follicles, blood estradiol, and progesterone levels did not correlate with antral CSA (p = .590, p = .104, and p = .511, respectively). In conclusion, neither preoperative anxiety nor extensive ovarian stimulation affects gastric size in fasting healthy patients. However, further studies are warranted in this area to define these findings better. Trial registration: Clinicaltrials.gov, identifier: NCT04833530